Pengaruh Bobot Biji terhadap Pertumbuhan Semai Petai (Parkia speciosa Hassk.) - Ni Luh Putu Indriyani; Deni Emilda (Universitas Pattimura, 2020)
One of the horticultural commodities included in the national seed provision program in 2018 is a stinking bean. The aim of the research was to determine the effect of seed weight on stink bean seedling growth. The research was conducted at Sumani Research Station, Indonesian Tropical Fruit Research Institute, from September to December 2017. A Complete Randomized Block Design was used in this study consisted of 5 treatments and 4 replications. The treatments were stink bean seed weights, namely: A) 1.5-1.8 g; B) 1.9-2.2 g; C) 2.3-2.6 g; D) 2.7-3 g; and E) > 3 g. The observed variables were plant height, stem diameter, leaf number, leaflet number, total dry weight of plants, length of roots, and a number of living seedlings. Data analysis used analysis of variance (ANOVA) and was proceeded with HSD test at Î± 5% if these treatments given gave significantly different effects. The results showed that the stink bean seed weight significantly affected the growth parameters of seedlings, including plant height, stem diameter, leaflet number, dry weights (of roots, upper parts of plants, and total) at 12 weeks after sowing. The seedlings from seeds weighing >3 g had the highest plant height, stem diameter, leaflet number, and dry weight (of roots, upper parts of plants, and total) compared to those seedlings from smaller seeds. Keywords: stink bean, seed weight, seedling growth ABSTRAK Salah satu komoditas hortikultura yang termasuk dalam program perbenihan nasional pada tahun 2018 adalah petai. Penelitian bertujuan untuk mengetahui pengaruh bobot biji terhadap pertumbuhan semai petai. Penelitian dilakukan di KP Sumani, Balai Penelitian Tanaman Buah Tropika, mulai bulan September sampai Desember 2017. Penelitian menggunakan rancangan acak kelompok lengkap dengan lima perlakuan dan empat ulangan. Perlakuan adalah bobot biji petai, yaitu: A) 1,5-1,8 g; B) 1,9-2,2 g; C) 2,3-2,6 g; D) 2,7-3 g; dan E) > 3 g. Peubah yang diamati adalah tinggi tanaman, diameter batang, jumlah daun, jumlah anak daun,bobot kering total tanaman, panjang akar dan jumlah benih hidup. Data dianalisis dengan menggunakan analisis ragam dan dilanjutkan dengan uji beda BNJ 5% jika perlakuan yang diberikan memberikan pengaruh yang nyata. Penelitian menunjukkan bahwa bobot biji petai berpengaruh nyata terhadap parameter pertumbuhan, seperti tinggi tanaman, diameter batang, jumlah anak daun, bobot kering (akar, bagian atas tanaman dan total) pada umur 12 minggu setelah semai. Semaian dari biji dengan bobot > 3 g mempunyai tinggi tanaman, diameter batang, jumlah anak daun dan bobot kering (akar, bagian atas tanaman dan total) yang terbesar dibandingkan bibit-bibit dari biji-biji yang lebih kecil. Kata kunci: bobot biji, pertumbuhan bibit, petai